Tinjauan Pelaksanaan Prosedur Pelepasan Informasi Rekam Medis untuk Klaim Asuransi Non-JKN di RSUD dr. R. Soetrasno Rembang - Bayu Eko Wahyudi; Rizkiyatul Amalia (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
The use of medical records for reimbursement of medical expenses or insurance claims that state the identity of the patient must obtain written consent from the patient or his heirs. Based on preliminary observations at RSUD dr. R. Soetrasno Rembang, it is known that 24 requests for medical record information for non-JKN insurance claims from April to June 2020, 75% of which found requests that did not comply with standard operating procedures, namely the absence of patients’ written consent. The purpose of this study was to describe the implementation of the procedure for releasing medical record information for non-JKN insurance claims at RSUD dr. R. Soetrasno Rembang. This type of research is descriptive qualitative. Data collection methods used are observation and interviews. The subjects of this study were information release officers, medical record unit management, insurance agent and part of the process of releasing medical record information. Data analysis used is non-statistical analysis technique. The results showed the implementation of procedure for releasing medical record information for non-JKN insurance claims at RSUD dr. R. Soetrasno Rembang is not accordance with the SOP, there are procedures that are not followed, namely requests for release of information are still being served even though they do not attach written consent from the patient.